Accuracy of navigated cam resection in femoroacetabular impingement: A randomised controlled trial. - Van Houcke, Jan; Khanduja, Vikas; Nakano, Naoki; Krekel, Peter; Pattyn, Christophe; Audenaert, Emmanuel (Wiley-Blackwell, 2017)
BACKGROUND: The main cause for revision hip arthroscopy surgery is incomplete bony resection of femoroacetabular impingement (FAI). This study aimed to compare the cam resection accuracy via the conventional hip arthroscopy technique with the navigation technique. METHODS: Two prospectively randomized groups were recruited: navigated (n = 15) and conventional (n = 14). A pre-operative CT and post-operative MRI scan were obtained in all cases to compare alpha angle, range of motion simulation and determine a pre-operative 3D surgical resection plan. RESULTS: Post-operatively, the mean maximal alpha angle improved significantly in the navigated group compared with the conventional group (55°vs.66°; P = 0.023), especially in the 12 o' clock position (45°vs.60°; P = 0.041). However, positioning time and radiation exposure were significantly longer in the navigated group. CONCLUSION: Navigated surgery is effective for patients with cam type FAI in helping restore normal anatomy, however, not without drawbacks. Larger studies will be required to validate our results.
Keywords: femoroacetabular impingement; hip arthroscopy; navigation